Evaluation of the accuracy of Demirjian's method for estimating chronological age from dental age in Shiraz, Iran: Using geometric morphometrics method - Masood Kermani; Fatemeh Tabatabaei Yazdi; Matin Abed Haghighi (Wiley, 2019)
Abstract Knowing the growth and developmental stages of a child or an adolescent allows for a comparison between their developmental and chronological age. The purpose of this study was to evaluate the accuracy of dental age estimation by Demirjian's method and to examine the applicability of Demirjian's method to Iranian children and adolescents. To do so, we investigated the relationship between chronological and dental age in a total of 158 children (81 female and 77 male) from Shiraz. The present study, for the first time, employs geometric morphometrics, a relatively new technique, to offer an accurate quantitative assessment of Demirjian's method. The correlation coefficient between chronological and dental age showed a significant relationship between dental age and chronological age. The average of the chronological age difference between girls and boys at the time of reaching the same stages of dental development was 0.77 years, which meant girls reached each stage of dental development 9 months earlier than their male peers. According to the results of this study, although the use of Demirjian's method in estimating the age of children in the city of Shiraz has acceptable accuracy, more precise studies are recommended to calibrate the method and develop a table adjusted to reflect development in the Iranian population.